Strenghening The Management Of Academic Quality At Primary And Medium Education In The Covid-19 Pandemic - Hadi Purnomo, M (International Journal of Educational Research & Social Sciences, 2021)
This paper discusses about strengthening the management of academic quality. Oneof the educational problems faced by the Indonesian, these are the low quality ofeducation at every level and unit of educations, especially at primary and mediumeducation. The various attempts have to improve the quality of national education,for instance: developing national or local curricula, increasing teacher’scompetences through training, procuring books and learning tools, improvingeducational facilities, infrastructures, and improving the quality of the school’smanagement. However, the indicators of the education’s quality do not show thesignificant improvement. Some schools, especially in cities show the quite encourageimprovements in the quality of education. But, part of them is still apprehensive,especially during the COVID-19 pandemic. The teachers and education’smanagement have experiencesin many things.